Religious Character Resilience: Dissecting the Roots of Students' Noble Character through Tri-Center of Education Habituation - Adinda Hasna Sheleisya; Udin Supriadi; Agus Fakhruddin (At- Ta'lim : Jurnal Pendidikan, 2026)
The cultivation of noble character is often solely attributed to formal educational institutions, whereas student character resilience is fundamentally rooted in the consistency of habituation beyond the school environment. This study aims to analyze the origins of noble character formation through the lens of the Tri-Center of Education, focusing on the integration of family and community environments. Employing a descriptive qualitative method, research subjects at SMKN 1 Bandung were selected using a purposive sampling technique with multi-source validation involving Islamic Education (PAI) teachers, Guidance and Counseling (BK) teachers, student affairs coordinators, and leaders of student organizations. Data were collected through recommendation instruments based on the Pancasila Student Profile indicators and screening questionnaires to capture the balance of student behavior, which were analyzed qualitatively as non-test instruments for initial subject selection without statistical testing. The scientific findings indicate that the religious character resilience of students with noble character at school is sustained by the synergy of specific external factors: morning discipline and role modeling by teachers at school, coupled with maternal trust and dialogic parenting at home. The findings also highlight the consistency of religious habituation and responsiveness to guidance within the family environment, as well as active involvement in socio-religious contributions within the community. The study concludes that character development is the manifestation of behavioral consistency, where moral actions in the domestic sphere align with public actions at school, remaining stable even when free from external surveillance. This research implies the importance of standardizing character criteria that are integrated across school, home, and social environments.